2020
DOI: 10.3389/fpubh.2020.00143
|View full text |Cite
|
Sign up to set email alerts
|

Knowing Your Audience: A Typology of Smoke Sense Participants to Inform Wildfire Smoke Health Risk Communication

Abstract: Central to public health risk communication is understanding the perspectives and shared values among individuals who need the information. Using the responses from a Smoke Sense citizen science project, we examined perspectives on the issue of wildfire smoke as a health risk in relation to an individual's preparedness to adopt recommended health behaviors. The Smoke Sense smartphone application provides wildfire-related health risk resources and invites participants to record their perspectives on the issue o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 11 publications
0
31
0
Order By: Relevance
“…Twenty-four household interviews conducted during a wildfire emergency in Australia found that smoke exposure messages were not timely or practical enough, and that they competed with fire risk messages ( 7 ). Analyses of SmokeSense (a mobile phone application) user data in the US found that message uptake depended more on individual receptiveness than on demographic factors ( 8 ). Lastly, a case report from the 2007 San Diego fires revealed that non-English speaking communities, including migrant and undocumented individuals are less likely to receive or understand messages; moreover, fear of deportation was considered more risky than the fires or smoke ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-four household interviews conducted during a wildfire emergency in Australia found that smoke exposure messages were not timely or practical enough, and that they competed with fire risk messages ( 7 ). Analyses of SmokeSense (a mobile phone application) user data in the US found that message uptake depended more on individual receptiveness than on demographic factors ( 8 ). Lastly, a case report from the 2007 San Diego fires revealed that non-English speaking communities, including migrant and undocumented individuals are less likely to receive or understand messages; moreover, fear of deportation was considered more risky than the fires or smoke ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another possible explanation for the non-significant findings around high-efficacy language and message comprehension could be due to the subject of air quality information itself. In the United States, the comprehension of air quality varies by previous experience with wildfire smoke, health status, risk perceptions, and various other factors [49]. In this study, more information about access to exposure-reducing resources from the university as well as from students' previous hometowns could elaborate on the baseline comprehension this sample has for air quality information.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, previous studies suggest that efficacy, risk perceptions, and worry are more resistant to change given greater familiarity and experience [ 82 , 86 , 87 ]. [ 88 ] suggested that enhancing perceived self-efficacy may be one fruitful way to motivate people who are at the “deciding stage” (cautious, proactive, and susceptible) to take action, potentially coinciding with lower levels of threat familiarity. Future study could explore how malleable these factors are for less familiar threats, and more explicit risk communications targeting efficacy could enhance perceptions of self- and response-efficacy.…”
Section: Discussionmentioning
confidence: 99%